Use of COI, CytB and ND5 genes for intra- and inter-specific differentiation of Haematobia irritans and Haematobia exigua - Low, Van Lun; Tan, T.K.; Domingues, L.N.; Tay, Sun Tee; Lim, Yvonne Ai Lian; Goh, T.G.; Panchadcharam, C.; Bathmanaban, P.; Sofian-Azirun, Mohd (Elsevier, 2014)
A multilocus sequence analysis using mitochondria-encoded cytochrome c oxidase subunit I (COI), cytochrome B (CytB), NADH dehydrogenase subunit 5 (ND5); nuclear encoded 18S ribosomal RNA (18S) and 28S ribosomal RNA (28S) genes was performed to determine the levels of genetic variation between the closely related species Haematobia irritans Linnaeus and Haematobia exigua de Meijere. Among these five genes, ND5 and CytB genes were found to be more variable and informative in resolving the interspecific relationships of both species. In contrast, the COI gene was more valuable in inferring the intraspecific relationships. The ribosomal 18S and 28S sequences of H. irritans and H. exigua were highly conserved with limited intra- and inter-specific variation. Molecular evidence presented in this study demonstrated that both flies are genetically distinct and could be differentiated based on sequence analysis of mitochondrial genes.